Effect of different shooting techniques in floorball on accuracy and velocity in experienced male floorball players - van den Tillaar, R. (Motor control, 2018)
The aims of this study were to investigate the effect of four different shooting techniques (slap, sweeper, drag, and wrist shots) in floorball on velocity and accuracy in experienced floorball players, and to investigate whether target height has an influence on these shooting performances. Ten experienced male floorball players (age, 21 ± 4years; body mass, 81.5 ± 10kg; body height, 1.85 ± 0.07m; and years of experience, 6.9 ± 3.1years) shot as hard as possible and tried to hit the upper and lower targets with four different shooting techniques from a 4-m distance. The main findings were that shooting techniques and target height could influence ball velocity in the expected way from slap to sweeper shots and drag to wrist shots, whereas accuracy did not change, and thereby, did not follow any velocity-accuracy trade-off like Fitts' law.